Implementation of competence by design in Canadian neurosurgery residency programs*. (3rd April 2022) - Cadieux, Magalie; Healy, Michael; Petrusa, Emil; Cooke, Lara; Traeger, Lara; Kesselheim, Jennifer C.; Riva-Cambrin, Jay; Phitayakorn, Roy
Abstract: Objective: The Royal College of Physicians and Surgeons of Canada (RCPSC) recently redesigned the Canadian neurosurgery residency training curriculum by implementing a competency-based model of training known as Competence by Design (CBD) centered around the assessment of Entrustable Professional Activities (EPAs). This sequential explanatory mixed-methods study evaluated potential benefits and pitfalls of CBD in Canadian neurosurgery residency education. Methods: Two four-month interval surveys were distributed to all Canadian neurosurgery residents participating in CBD. The surveys assessed important educational components: CBD knowledge of key stakeholders, potential system barriers, and educational/psychological impacts on residents. Paired t -tests were done to assess changes over time. Based on longitudinal survey responses, semi-structured interviews were conducted to investigate in-depth residents' experience with CBD in neurosurgery. The qualitative analysis followed an explanatory approach, and a thematic analysis was performed. Results: Surveys had 82% average response rate ( n  = 25). Over time, most residents self-reported that they retrospectively understood concepts around CBD intentions ( p  = 0.02). Perceived benefits included faculty evaluations with more feedback that was clearer and more objective (53% and 51%). Pitfalls included the amount of time needed to navigate through EPAs (90%) and residents forgetting to initiate EPA forms (71%). There was no significant change over time. During interviews, five key themes were found. Potential solutions identified by residents to enhance their experience included learning analytics data availability, mobile app refinement, and dedicated time to integrate EPAs in the workflow. Conclusion: This study was the first to assess resident-perceived benefits and pitfalls of the neurosurgery CBD training program in an educational framework context. In general, residents believed that theoretical principles behind CBD were valuable, but that technological ability and having enough time to request EPA assessments were significant barriers to success. Long-term studies are required to determine the definitive outcomes of CBD on residents' performance and ultimately, on patient care.